Work-related injuries in trade apprentices - Tim Driscoll; Margaret Hanson (Elsevier, 1997)
Abstract: This study attempted to identify and describe all work-related injuries in a cohort of trade apprentices at the Canberra Institute of Technology over an approximate one-year period. In 997 persons followed for a total of 198 456 days of exposure there were 771 injuries of which 191 were classed as serious (defined as at least one day off work and/or received sutures and/or required hospital treatment). The most common circumstance of injur) was a cut to the fingers or hand while using a sharp-edged, non-powered hand tool. At least 52 persons required hospital treatment and another 51 required suturing. Overall rates of injury were 222 (95 per cent confidence interval (CI) = 193 to 256) injuries per 1000 full time equivalents (FTEs) and 169 (95% CI=147 to 193) injured persons per 1000 persons. Injury rates adjusted for stage (year of course) were significantly different between schools and were highest in the construction and engineering trades groups (X25= 57.30, P < 0.001). There was a statistically significant trend of higher risk of injury with later stage after adjustment for school (X22= 6.34, P= 0.042). This study has shown that trade apprentices are at high risk of significant work-related injury and provides important insights into the characteristics of work-related injuries in trade apprentices. These have significant implications for the safety expectations apprentices may bring to the workplace and for the appropriate targeting of occupational health and safety training of apprentices in the trade occupations.